PERGESERAN BAHASA JAWA DALAM RANAH KELUARGA PADA MASYARAKAT MULTIBAHASA DI WILAYAH KABUPATEN BREBES - Hari Bakti Mardikantoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
Language contact and dialectal contact of social interaction at multilingual society in Brebes represent phenomenon draw to be studied from the perspective of sociolinguistics because this phenomenon has a correlation not only with language aspect, but also with social aspect of culture. This research aims to express 1) the pattern of Javanese shift in Brebes and 2) the social factor effect of culture in Javanese shift in Brebes. The result of this Research find that there is a Javanese shift of domain family multilingual society in Brebes. The Javanese shift happens in the pattern of Javanese shift including (a) the pattern of husband relation with wife, (b) the pattern of wife relation with husband, (c) the pattern of parents relation with child, (d) the pattern of child relation with pattern, and (d) the pattern of child relation with child. The Javanese shift in the domain family in Brebes is influenced by some social factors. The factor are (a) the speaking situation, (b) the ethnic background, (c) the ability of family members language, (d) the consanquinity relation, and (e) the topic of discussion.